ICSID 2016 Annual Report - International Centre for Settlement of Investment Disputes (World Bank Group, Washington, DC, 2016)
The ICSID Convention entered into force on October 14, 1966, making this year the 50th anniversary of the Convention and of the ICSID system of dispute settlement created by Member States under the Convention. As can be seen from the summary of highlights in the following section and the detailed overview of operations in Chapter 3, ICSID’s core function remains the provision of impartial, cost-effective and high quality dispute settlement services. In fiscal year 2016, the Centre fulfilled this function by registering 45 cases, administering a new record of 247 cases, constituting more than 70 tribunals, holding nearly 150 hearings in numerous locations, and concluding 51 cases.